Regiodivergent nucleophilic fluorination under hydrogen bonding catalysis: a computational and experimental study - Horwitz, MA; Dürr, AB; Afratis, K; Chen, Z; Soika, J; Christensen, KE; Fushimi, M; Paton, RS; Gouverneur, V (American Chemical Society, 2023)
The controlled programming of regiochemical outcomes in nucleophilic fluorination reactions with alkali metal fluoride is a problem yet to be solved. Herein, two synergistic approaches exploiting hydrogen bonding catalysis are presented. First, we demonstrate that modulating the charge density of fluoride with a hydrogen-bond donor urea catalyst directly influences the kinetic regioselectivity in the fluorination of dissymmetric aziridinium salts with aryl and ester substituents. Moreover, we report a urea-catalyzed formal dyotropic rearrangement, a thermodynamically controlled regiochemical editing process consisting of C–F bond scission followed by fluoride rebound. These findings offer a route to access enantioenriched fluoroamine regioisomers from a single chloroamine precursor, and more generally, new opportunities in regiodivergent asymmetric (bis)urea-based organocatalysis.